(untitled) (Revista de Ciências Agroveterinárias, 2018)
The objective of this study was to evaluate the effect of climatic conditions provided by two types of stalls on the physiological and behavioral responses of horses during agricultural exposure. The study was developed during 2014 and 2015 in an Agricultural Fair located in the semiarid region of the state of Minas Gerais, Brazil. Climatic environment, place of accommodation, physiological and behavioral variables of 114 Mangalarga Marchador horses, housed in individual metal and masonry stalls, were observed. Meteorological variables inside the metal and masonry stalls were monitored. Physiological variables were characterized by respiratory rate and body temperature. For behavioral analysis, the frequency of occurrence of defecation, urination, neigh, agitation, food and water intake were observed at 8 am, 10 am, 12 pm, 14 pm, 16 pm and 18 pm. The thermal environment was classified as thermal discomfort from 10 am. Respiratory rate and body temperature were outside ideal values. The metal stall caused greater thermal discomfort for horses.